Inequalities in multimorbidity among elderly: a population-based study in a city in Southern Brazil - Caroline dos Santos Costa; Thaynã Ramos Flores; Andrea Wendt; Rosália Garcia Neves; Elaine Tomasi; Juraci A. Cesar; Andrea Dâmaso Bertoldi; Virgílio Viana Ramires; Bruno Pereira Nunes (Cadernos de Saúde Pública, 2018)
Lower socioeconomic level is positively related to multimorbidity and it is possible that the clustering of health conditions carries the same association. The aim of this study was to identify prevalence of multimorbidity and clusters of health conditions among elderly, as well the underlying socioeconomic inequalities. This was a cross-sectional population-based study carried out with 60-year-old individuals. Multimorbidity was defined as the presence of 2+, 3+, 4+ or 5+ health conditions in the same individual. Schooling levels and the National Economic Index were used to investigate inequalities in the prevalence of multimorbidities among elderly. Slope and concentration indexes of inequality were used to evaluate absolute and relative differences. A factorial analysis was performed to identify disease clusters. In every ten older adults, about nine, eight, seven and six presented, respectvely, 2+, 3+, 4+ and 5+ health conditions. Three clusters of health conditions were found, involving musculoskeletal/mental/functional disorders, cardiometabolic, and respiratory factors. Higher inequalities were found the higher amount of health conditions (5+), when considering economic level, and for 3+, 4+ and 5+, when considering educational level. These findings show high multimorbidity prevalence among elderly, highlighting the persistence of health inequalities in Southern Brazil. Strategies by the health services need to focus on elderly at lower socioeconomic levels.